ISDC Feedback on CGIAR Portfolio Narrative 2025-2030 - CGIAR Independent Science for Development Council (2024)
In November 2024 the Independent Science for Development Council (ISDC) received and reviewed the CGIAR Portfolio Narrative 2025-2030 (Narrative). Because of the diverse audiences that use ISDC’s assessment, the feedback is structured in three sections, providing a mix of high-level considerations while also providing details and questions for future inquiries during the Portfolio Inception Phase.